Rechallenge of immunotherapy beyond progression in patients with extensive-stage small-cell lung cancer - Li, Lingling; Liu, Tingting; Liu, Qingyan; Mu, Shuai; Tao, Haitao; Yang, Xuhui; Li, Yao; Xiong, Qi; Wang, Lijie; Hu, Yi (Frontiers in Pharmacology, 2022)
Background: Rechallenge of immunotherapy beyond progression (RIBP) has been demonstrably effective in a variety of cancers. Our study aims to investigate the efficacy of RIBP in small-cell lung cancer (SCLC) patients under real-world conditions. Methods: SCLC patients who experienced progressive disease after receiving programmed cell death-1 (PD-1) / programmed cell death ligand-1 (PD-L1) inhibitors combined with chemotherapy from Jan 2017 to Oct 2021 were enrolled. The study population was divided into two groups: the RIBP group and the discontinuation of immunotherapy beyond progression (DIBP) group. Inverse propensity score weighting (IPSW) method was used to balance the clinical baseline characteristics. The short-term and long-term efficacy of the two groups was compared. Results: 100 SCLC patients were included in this study. There were 45 patients in the RIBP group and 55 patients in the DIBP group. The disease control rate (DCR) and the proportion of durable clinical benefit (DCB) were significantly higher in the RIBP group (DCR: 79.7% vs 55.7%, P = 0.027; DCB: 40.7% vs 20.7%, P = 0.025) after weighting. The median progressive-free survival (PFS) in the RIBP group was significantly longer than the DIBP group in the total population (mPFS: 4.8 vs 2.4 months, P = 0.002), while there was no significant difference in overall survival (OS) of the two groups (mOS: 17.4 vs 8.0 months, P = 0.098). In the weighted first-line initial immunotherapy subgroup, PFS and OS were significantly improved in the RIBP group (mPFS: 4.5 vs 2.8 months, P = 0.017; mOS: 11.6 vs 5.4 months, P = 0.028). After weighting, the RIBP group had a significantly longer PFS than the DIBP group in the SD/PD response to the initial immunotherapy subgroup (mPFS: 6.8 vs 1.8 months, P = 0.026). Conclusions: Rechallenge of PD-1/PD-L1 inhibitors could bring benefits to SCLC patients, especially in the first-line initial immunotherapy subgroup or SD/PD response to the initial immunotherapy subgroup.